A Theory of Urban Squatting and Land-Tenure Formalization in Developing Countries - Brueckner, Jan K. (2012)
This paper offers a new theoretical approach to urban squatting, reflecting the view that squatters and formal residents compete for land within a city. The key implication is that squatters "squeeze" the formal market, raising the price paid by formal residents. The squatter organizer ensures that squeezing is not too severe, since otherwise, the formal price will rise to a level that invites eviction by landowners. Because eviction is absent in equilibrium, the model differs from previous analytical frameworks, where eviction occurs with some probability. It also facilitates a general equilibrium analysis of squatter formalization policies.